Building Resilience of Farming Landscape Through Climate Smart Agriculture Hub - Yeboah, Stephen; Adomako, Joseph; Amankwa, Patricia; Narveh, Ernestina; Frimpong-Anin, Kofi; Haleegoah, Joyce; Adablah, Richard (2024)
The Climate Smart Agriculture Hub (CSA) is a key scaling ecosystem platform for scaling AICCRA technology in Ghana. The hub connects all the key actors along the scaling value chain including researchers, extension officers, radio extension actors, ag-innovators, agro SME, and climate information service providers. Selecting and training CSA Hub members have become crucial to support the downscaling of CIS-CSA technologies at the community level. Climate-smart agriculture training increases the resilience of smallholder farmers through the adoption of climate-smart agriculture technologies that will make crops more resilient and improve smallholder agriculture systems. This training aimed to help scale CSA technologies across Ghana to build a more resilient agricultural system.